REKONSTRUKSI MASA JABATAN ANGGOTA LEGISLATIF PERSPEKTIF DEMOKRASI PANCASILA - M Syamsudin (JIL : Journal of Indonesian Law, 2021)
AbstractThe term limit of members of legislative council has become debatable every time an election is about to be held, it becomes a dilemma when the constitution provides equal opportunities for every citizen to sit in government. In fact, most members of parliament are actually filled with old members. So far, Indonesia has no clear regulation regarding the term limit for the members of legislative council. Based on the initial research, it is important to reconsider the term limit. It can be done through two stages, first, revising the MD3 Law by adding the phrase limiting the term of members of legislative council which is two terms or by implementing the second stage by amending the 1945 Constitution of Republic of Indonesia by adding an article regarding the term limit of members of the legislative council, which is two terms. So far, because there was no regulation about the term limit, it has violated the constitution as well as the spirit and principles of Pancasila democracy. First, it has violated the principle of democracy because there was no regulation that limit the term of becoming the member of legislative council that resulted in the in the lack of new regeneration or new member in the legislative council so that there is no justice according to the 5th principle of Pancasila. Second, it has violated the principle of deliberation (musyawarah), because it led to the Abuse of Power. Besides, it has violated the principle of human rights as well, since the people’s right to participate in the government is limited because there was no clear regulation stated the term limit for those who sit in the legislative council.AbstrakMasa Jabatan anggota Legislatif selalu menjadi perdebatan setiap kali akan dilaksanakan Pemilu, menjadi delamatis ketika konstitusi memberikan peluang yang sama bagi setiap warga negara untuk duduk di pemerintahan, namun kenyataanya sebagian besar anggota parlemen justru diisi oleh wajah-wajah yang lama. Indonesia selama ini belum ada pengaturan yang jelas terkait dengan masa jabatan anggota legislatif. Berdasarkan penelitian yang dilakukan oleh penulis, Rekonstruksi masa jabatan anggota legislatif penting untuk dilakukan, hal tersebut dapat ditempuh melalui dua mekanisme pertama, melakukan revisi UU MD3 dengan menambahkan frasa pembatasan masa jabatan anggota legislatif yaitu dua kali masa jabatan atau dengan mekanisme yang kedua, melakukan amandemen UUD 1945 dengan menambahkan pasal tentang masa jabatan anggota legislatif yaitu dua kali masa jabatan. Selama ini, ketiadaan pembatasan masa jabatan anggota legislatif telah mencidrai konstitusi juga semanggat dan asas demokrasi Pancasila yakni pertama menciderai asas kerakyatan, dengan tidak adanya pembatasan masa jabatan anggota legislatif menjadikan kurangnya regenerasi baru di legislatif sehingga tidak adanya keadilan sesuai sila ke-5 Pancasila, kedua mencidrai asas musyawarah, dengan tidak adanya pembatasan masa jabatan legislatif rentan adanya Abuse of Power (penyalahgunaan kekuasaan), ketiga menciderai asas menjamin HAM, karena dengan tidak adanya pembatasan masa jabatan anggota legislatif bearti membatasi setiap warga negara untuk ikut serta dalam pemerintahan.